Is unassisted smoking cessation choice and success associated with high mental stress? Evidence from six cities in China - Yang, Tingzhong; Cottrell, Randall R.; Wu, Dan (Tobacco induced diseases, 2024)
Unassisted smoking cessation (USC) is a method of quitting smoking driven by self-determination without the support of professional cessation assistance. This approach may contribute to a potential decrease in overall smoking prevalence within a population. However, the factors potentially influencing smokers' choice of USC and their success remain unclear. This study examined the associations between mental stress and USC choice and success. Between June and September 2016, a cross-sectional multistage sampling design was used to interview subjects from six selected cities in China. A standardized questionnaire was used to obtain information on sociodemographic characteristics, USC choice, and success. Mental stress was measured by the Chinese version of the Perceived Stress Scale (CPSS). Multivariate logistic regression models were used to examine the association between mental stress, USC choice, and success, with adjustments for relevant covariates. Among 1647 smokers who had attempted or had quit, 91.6% (95% CI: 90.9-97.5) reported that they had done so without assistance, and 42.1% (95% CI: 32.4-61.3) of them achieved abstinence. While mental stress was not significantly associated with USC success (χ =2.02, p=0.1547), smokers experiencing high levels of mental stress were 0.34 times less likely (95% CI: 0.23-0.50) to attempt USC compared to those with low levels of mental stress. Moreover, a significant negative linear association was observed between varying levels of mental stress and the prevalence of USC use (R =0.910, p<0.001). The study findings should help to understand USC and its role in reducing smoking prevalence in the Chinese population. These findings can inform future tobacco control programs and policies in China. Government and social agencies should prioritize understanding smokers' preferences for USC and providing USC services to promote success within the population.